Comparative performance assessment of the most commonly used personnel radiation dosimeters in Nigeria - Yahaya, Bappah S.; Ibrahim, Umar; A. Mundi, Abdullahi; M. Idris, Mustapha; A. Bilya, Musa; Mohammed, Anas; Ali G., Musa (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
Radiation dosimeters exhibit several performance properties characterized by their precision and accuracy, linearity, dose and energy dependence, stability and spatial resolution. However, these characteristics may not be satisfied by all dosimeters. The dosimetric performances of Instadose and Thermolumniscence dosimeters (TLDs) which are the two most commonly used personal dosimeters in health care institutions were comparatively assessed under clinical settings in which a GE haulum XR 6000 X-ray machine with a frequency of 50/60 Hz was used to serially irradiate Mironinstadose and TLD 100H badges to a controlled exposure factors and readings of absorbed doses for instadose were obtained from a portable computer with internet access, while that of TLDs was obtained through heating using Harshaw 4500 automatic TLD reader at Center for Energy Research and Training (CERT), Zaria. The dose equivalent quantities measured were; Hp (10), Hp (3) and Hp(0.07) all in mSv, representing deep, eye lens and shallow doses respectively. Results of measured doses ranged between 0.74 mSv to 22.96 mSv for instadose and 0.71 mSv to 35.42 mSv for TLD badges in all performance tests conducted. Homogeneity results were 9% and 12%, reproducibility was 7.2% and 3.9% while percentage deviation for linearity test was below 10% for both instadose and TL dosimeters. The performance tests results of instadose and TL dosimeters were assessed based on the criteria of the International Electrotechnical Commission (IEC) 1066 standard. The assessment revealed good performance indices within the requirement of the IEC standard. However, TL dosimeters demonstrate high sensitivity in the self-irradiation test exceeding the standard mSv values.